2002
DOI: 10.1023/a:1016419906546
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: High-fiber diet supplementation is commonly used in IBS, although it poses several management problems. Partially hydrolyzed guar gum (PHGG) has shown beneficial effects in animal and human studies, but its potential role in IBS symptom relief has not been evaluated yet. We investigated PHGG in IBS patients and compared it to a wheat bran diet. Abdominal pain, bowel habits, and subjective overall rating were longitudinally evaluated in 188 adult IBS patients (139 women and 49 men) for 12 weeks. Patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Furthermore, the absence of common bran products such as fructanes might also support beneficial effects for people with irritable bowel syndrome (IBS). More fiber used in those patients has been shown to be supportive [22,23]. Fecal bulk was significantly increased by the extrinsic wheat fiber-enriched diet in the form of solid foods given as muffins, rolls, pizza, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the absence of common bran products such as fructanes might also support beneficial effects for people with irritable bowel syndrome (IBS). More fiber used in those patients has been shown to be supportive [22,23]. Fecal bulk was significantly increased by the extrinsic wheat fiber-enriched diet in the form of solid foods given as muffins, rolls, pizza, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble, non-viscous fiber may also be potentially useful in alleviating symptoms of inflammatory conditions, such as irritable bowel syndrome (IBS). In particular, partially hydrolyzed guar gum has been shown to improve abdominal pain and bowel habits better than wheat bran and qualitative scores of epithelial injury and inflammation compared to control [51]. …”
Section: Health Benefits Of Fibermentioning
confidence: 99%
“…This study, performed in order to assess the effects of PHGG in IBS, confirmed the beneficial effect of this therapeutic strategy, in line with previous experiences. [ 16 17 18 19 20 ] In particular, we observed an overall improvement of the abdominal swelling, an increase in the number and quality of evacuations and a reduction in the CTT. On the other hand, abdominal pain did not significantly improve, further confirming previous findings.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, abdominal pain did not significantly improve, further confirming previous findings. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%